The amenity value of climate to German households - Katrin Rehdanz; David Maddison (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This study uses the hedonic approach to measure the amenity value of climate in Germany. Unlike in earlier research separate hedonic wage and house price regressions are estimated for relatively small geographic areas and formal tests undertaken to determine whether the coefficients describing the impact of climate variables are homogenous across these areas. Evidence suggests that German households are compensated for climate amenities mainly through hedonic housing markets. Given that climate is largely unproductive to industry and few industries spend more on land than labour this is consistent with what theory would predict. Throughout Germany house prices are higher in areas with higher January temperatures, lower July temperatures and lower January precipitation. In East Germany wages are higher in areas with higher January precipitation. The full implicit price of climate variables however is very uncertain.
Keywords: Q29; R29; 330; Climate Change; Germany; Hedonic Pricing; Klima; Hedonischer Preis; Regionale Lohnstruktur; Immobilienpreis; Miete; Schätzung; Deutschland